Acute Endocrine and Force Responses and Long-Term Adaptations to Same-Session Combined Strength and Endurance Training in Women. (January 2016) - Eklund, Daniela; Schumann, Moritz; Kraemer, William J.; Izquierdo, Mikel; Taipale, Ritva S.; Häkkinen, Keijo
Abstract : Abstract: Eklund, D, Schumann, M, Kraemer, WJ, Izquierdo, M, Taipale, RS, and Häkkinen, K. Acute endocrine and force responses and long-term adaptations to same-session combined strength and endurance training in women. J Strength Cond Res 30(1): 164–175, 2016—This study examined acute hormone and force responses and strength and endurance performance and muscle hypertrophy before and after 24 weeks of same-session combined strength and endurance training in previously untrained women. Subjects were assigned 1 of 2 training orders: endurance preceding strength (E + S, n = 15) or vice versa (S + E, n = 14). Acute force and hormone responses to a combined loading (continuous cycling and a leg press protocol in the assigned order) were measured. Additionally, leg press 1 repetition maximum (1RM), maximal workload during cycling (Wmax), and muscle cross-sectional area (CSA) were assessed. Loading-induced decreases in force were significant ( p < 0.01–0.001) before (E + S = 20 ± 11%, S + E = 18 ± 5%) and after (E + S = 24 ± 6%, S + E = 22 ± 8%) training. Recovery was completed within 24 hours in both groups. The acute growth hormone (GH) response was significantly ( p < 0.001) higher after S + E than E + S at both weeks 0 and 24. Testosterone was significantly ( p < 0.001) elevated only after the S + E loading at week 24 but was not significantly different from E + S. Both groups significantly ( p < 0.001) improved 1RM (E + S = 13 ± 12%, S + E = 16 ± 10%), Wmax (E + S = 21 ± 10%, S + E = 16 ± 12%), and CSA (E + S = 15 ± 10%, S + E = 11 ± 8%). This study showed that the acute GH response to combined endurance and strength loadings was significantly larger in S + E compared with E + S both before and after 24 weeks of same-session combined training. Strength and endurance performance and CSA increased to similar extents in both groups during 24 weeks despite differences in the kinetics of GH. Previously untrained women can improve performance and increase muscle CSA using either exercise order.